Value chain analysis of Large Cardamom (Amomum subulatum Roxburg) in Bhojpur, Nepal - Kalauni, Dharmendra; Joshi, Arati (Journal of Agriculture and Natural Resources, 2020)
Large Cardamom is a high value spice crop having substantial export potential. The study was conducted on Feb-May, 2019 in Arun rural municipality, Bhojpur municipality and Sadananda municipality with an objective to analyze existing value chain of Large Cardamom in Bhojpur district of Nepal. In total, 150 Large Cardamom growers were selected using purposive sampling technique. In addition to that, 17 traders from the Bhojpur, Khadbari and Birtamod were also selected for the study. Findings showed that farmers were interested in Large Cardamom industry due to good return and high profit margin per unit of commodity. The benefit-cost ratio was found higher in Arun village municipality (1.735), followed by Sadananda municipality (1.467) and Bhojpur municipality (1.263). Increasing disease and pest attack and low seasonal price are the major problem in production and marketing of Large Cardamom respectively. Harvested capsules of Large Cardamom were dried using traditional drier (bhatti) that make the dried capsules prone to quality degradation. Value addition practices such as grading, tail cutting were found poor in farmer level. Producer’s share and marketing efficiency were found highest when farmers sell their product directly to exporter and lowest in domestic market channel. Demand and supply of Large Cardamom in Indian market was most determining factor for price fixation of Nepalese Large Cardamom. Thus from the study it is recommended to improve production process through appropriate mechanization, along with possible efforts in identification of potential international markets and possible ways for direct export to third countries which could help farmers to receive higher price.